Elucidation of the centromere involvement in an inversion (13) by fluorescent in situ hybridisation. Issue 5 (May 1993) - Gordon, P L; Dalton, J D; Martens, P R; Tharapel, A T; Wilroy, R S
Abstract : A newborn infant with phenotypic features of trisomy for distal 13q was found to have recombinant inversion duplication involving the (13)(q22-->qter) region. Parental karyotypes showed that the mother had a normal 46, XX complement and the father had an apparently balanced pericentric inversion of a chromosome 13. Because of the unusual nature of the inversion, the exact position of the centromere on the father's inverted chromosome 13 was difficult to assign by GTG banding, even on prometaphase chromosomes. CBG and NOR banding were not informative in determining the location of the centromere. Fluorescent in situ hybridisation with an alpha satellite DNA probe for D13Z1/D21Z1 helped in confirming the exact position of the centromere in the rearranged paternal chromosome. Thus, the origin of the proband's abnormal chromosome 13 was clarified.